1993
DOI: 10.1007/bf01696346
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic recovery following high-dose combined alkylating-agent chemotherapy and autologous bone marrow support in patients in phase-I clinical trials of colony-stimulating factors: G-CSF, GM-CSF, IL-1, IL-2, M-CSF

Abstract: Hematopoietic recovery in 115 patients with metastatic breast cancer or metastatic melanoma, enrolled in phase-I studies of recombinant growth factors while undergoing treatment with high-dose chemotherapy with autologous bone marrow support, was examined with assays of bone marrow progenitor cells and peripheral blood progenitor cells, and by evaluation of peripheral blood counts. Groups of patients receiving hematopoietic cytokine support [with interleukin-1 (IL-1), interleukin-2 (IL-2), granulocyte colony-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…These observations are similar to those described by Laughlin et al, 26 who reported no relevant modifications of marrow regeneration using continous intravenous infusion of similar doses of IL-2 (40 000 Cetus units m 2 /day equivalent to 240 000 IU m 2 /day) early after BMT. Similarly, Meehan et al 27 observed no modification of engraftment time using higher IL-2 dosages (600 000 IU m 2 /day) subcutaneously.…”
Section: Discussionsupporting
confidence: 91%
“…These observations are similar to those described by Laughlin et al, 26 who reported no relevant modifications of marrow regeneration using continous intravenous infusion of similar doses of IL-2 (40 000 Cetus units m 2 /day equivalent to 240 000 IU m 2 /day) early after BMT. Similarly, Meehan et al 27 observed no modification of engraftment time using higher IL-2 dosages (600 000 IU m 2 /day) subcutaneously.…”
Section: Discussionsupporting
confidence: 91%
“…Acute toxicities of either IL-1α or IL-1ÎČ were greater following intravenous compared to subcutaneous injection; subcutaneous injection was associated with significant local pain, erythema and swelling. 34 Chills and fever are observed in nearly all patients, even in the 1 ng/kg dose group. 35 At 10-30 ng/kg, all patients experience chills and fever.…”
Section: Interleukin-1mentioning
confidence: 98%
“…Administration of recombinant human G-CSF protein has been shown to significantly accelerate the recovery of white blood cell counts, following either the administration of cytotoxic agents or bone marrow transplantation (29,30). Recombinant human G-CSF is now approved by the FDA for treatment of myelosuppression in human patients (30) and is thus relevant for use as a potential gene therapy.…”
Section: Circulating and Tissue Levels Of Human G-csf Protein Followimentioning
confidence: 99%